Diet and Mental Health: Review of the Recent Updates on Molecular Mechanisms - Justyna Godos; Walter Currenti; Donato Angelino; Pedro Mena; Sabrina Castellano; Filippo Caraci; Fabio Galvano; Daniele Del Rio; Raffaele Ferri; Giuseppe Grosso (MDPI AG, 2020)
Over the last decades, there has been a substantial increase in the prevalence of mental health disorders, including an increased prevalence of depression, anxiety, cognitive, and sleep disorders. Diet and its bioactive components have been recognized among the modifiable risk factors, possibly influencing their pathogenesis. This review aimed to summarize molecular mechanisms underlying the putative beneficial effects toward brain health of different dietary factors, such as micro- and macronutrient intake and habits, such as feeding time and circadian rhythm. The role of hormonal homeostasis in the context of glucose metabolism and adiponectin regulation and its impact on systemic and neuro-inflammation has also been considered and deepened. In addition, the effect of individual bioactive molecules exerting antioxidant activities and acting as anti-inflammatory agents, such as omega-3 fatty acids and polyphenols, considered beneficial for the central nervous system via modulation of adult neurogenesis, synaptic and neuronal plasticity, and microglia activation has been summarized. An overview of the regulation of the gut-brain axis and its effect on the modulation of systemic inflammation and oxidative stress has been provided. Finally, the impact of bioactive molecules on inflammation and oxidative stress and its association with brain health has been summarized.